Evaluation of Pixelated Plastic Scintillators Coupled to Multi-Channel Silicon Photomultipliers for Beta-Ray Detection and Source Localization - Rachman, Agus Nur; Kurniawan, Rusbani; Ekaranti, Egnes; Wahyudi, Wahyudi; Nugraha, Eka Djatnika; Ngarayana, I Wayan; Hamdan, Moh (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
This paper presents a novel detector design for radiation detection technology, based on pixelated plastic scintillators coupled to multi-channel silicon photomultipliers (SiPMs). This detector combines the efficiency of plastic scintillators with the sensitivity and versatility of SiPMs, Overcoming the limitations of traditional photomultiplier tubes in terms of durability, power consumption, and sensitivity. The compact and modular nature of the detector makes it suitable for diverse environments and applications, such as portable radiation monitoring devices or integration into existing experimental setups. The performance of the detector was evaluated using beta-ray sources of 36Cl and 90Sr, and it was demonstrated that the detector can detect and localize the point source with high accuracy and resolution.